On the suitability of high vacuum electrospray deposition for the fabrication of molecular electronic devices - Temperton, Robert H.; O'Shea, James N.; Scurr, David J. (Elsevier, 2017)
We present a series of three studies investigating the potential application of high vacuum electrospray deposition to construct molecular electronic devices. Through the use of time of flight secondary ion mass spectrometry we explore the use of this novel deposition technique to fabricating multilayer structures using materials that are compatible with the same solvents and films containing a mixture of molecules from orthogonal solvents. Using x-ray photoelectron spectroscopy we study the deposition of a polymer blend using electrospray and find evidence of preferential deposition of one of the components.